On how morphology spreads. (July 2021) - Gardani, Francesco
Abstract : A language's grammar can be stratified, due to borrowing processes. While being a well-established term in the linguistic literature, the term 'borrowing' is sometimes used in a non-uniform way, particularly when it applies to bound morphological formatives. A Stratal Effect is hypothesized, which, applying to varying extent, gives rise to at least three distinct, psycholinguistically motivated types of morphological transfer. A typology of morphological spread is proposed, which consists of three main types: strictly compartmentalized co-morphologies, partially compartmentalized co-morphologies, and morphological borrowing. The widespread view that affix borrowing can be either direct or indirect is questioned and it is argued that most likely, morphological borrowing is always an intermediate process, involving the extraction of formatives and their diffusion within the lexicon.